Study of economic and financial feasibility of appropriate technology for crab cultivation using the crab ball method as the development of the blue economy concept in mangrove areas - Dinar Ari Prasetyo (Enrichment : Journal of Management, 2023)
In addition to implementing appropriate technology that corresponds to the character and potential of the region, which in this case is the mangrove area, and focusing on increasing the economic benefits for villages and communities, the implementation of TTG also must pay attention to the environmental ecosystem. It is accordance with the concept of the blue economy. An appropriate technology that can be used for developing economic activity in the mangrove area but does not interfere with ecosystems is the crab breeding system, using the crab ball method. Crab ball is one of the methods for inserting crabs into a tool called a crab ball, where the use of the tool is not only friendly to the forest ecosystem, but also does not require a large financial investment. One of the areas with mangrove potential is in Tirtihargo Village, Bantul District, Yogyakarta. In this study, a feasibility study was conducted from the economic and financial sides to look at the potential of the implementation of this TTG. To measure the viability of the implementation of technology for the proper cultivation of crabs using the crab ball method using two analyses namely economic feasibility and financial feasibility analysis. On economic feasibility analysis using the benefit-cost ratio approach as well as on financial feasibility analysis using the three financial ratio approaches (payback period, net present value, and internal rate of return). The results found that this implementation of appropriate technology is valid and profitable based on the principles of economic and financial analysis criteria.